1998
DOI: 10.1046/j.1365-2427.1998.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface water–groundwater exchanges in three dimensions on a backwater of the Rhône River

Abstract: 1. Hydrological exchange between the surface stream and the hyporheic zone is well documented in the main channel of rivers, especially at the reach scale. Hydrological processes of advection/convection occur at different scales, and in secondary channels of large rivers little is known about these exchanges in the hyporheic zone on a broad scale (i.e. kilometres). This work studied exchanges of water and biota in a secondary channel on a large scale (4 km), using a three‐dimensional framework. 2. The exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 84 publications
3
24
0
1
Order By: Relevance
“…Such variations are confirmed by this study and are shown to propagate to the hyporheic zone, although slightly attenuated, as already demonstrated in several studies in Alpine and other rivers (e.g. Brunke and Gonser, 1997;Dole-Olivier, 1998;Fowler and Scarsbrook, 2002). The thermal alterations related to the hydropeaking waves probably affect the composition of hyporheic assemblages in the Noce Stream.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such variations are confirmed by this study and are shown to propagate to the hyporheic zone, although slightly attenuated, as already demonstrated in several studies in Alpine and other rivers (e.g. Brunke and Gonser, 1997;Dole-Olivier, 1998;Fowler and Scarsbrook, 2002). The thermal alterations related to the hydropeaking waves probably affect the composition of hyporheic assemblages in the Noce Stream.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the hyporheic zone may provide a temperature refuge for epigean taxa (Boulton et al, 1998), and high surface water temperature may initiate the movement of some taxa into the hyporheic zone (Fowler and Scarsbrook, 2002). On the other hand, because in natural conditions, hyporheic temperatures are cooler in summer and warmer in winter relative to the water in the channel and less variable (Williams, 1984;Ward, 1994;Dole-Olivier, 1998), the imposed variation to the hyporheic thermal regime might limit the distribution of stygobite taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Dole-Olivier, 1998;Davy-Bowker et al, 2006;Mathers & Wood, 2016), the consequences of flow dynamics at small spatial scales and the associated sedimentary characteristics upon benthic and hyporheic invertebrate assemblages remain poorly quantified (Marmonier et al, 2010(Marmonier et al, , 2012Descloux et al, 2014;Jones et al, 2015). Despite several seminal papers over multiple decades which identified the potential importance of vertical hydraulic connectivity (Orghidan, 1959;Tilzer, 1968;Hynes, 1983), linkages between surface and groundwater and its influence on instream communities remain poorly studied (Boulton et al, 1999;Krause et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…These variations in the impact channel were mostly linked to higher specific conductance and VHG as well as lower water oxygenation at the downstream position compared to the upstream position (Figure 3a). Nevertheless, the differences between surface and interstitial water were very weak, and the amplitude of vertical changes in the parameters (Table 2) was minimal compared to other studies in which hyporheic water upwelled mixed with deep groundwater (e.g., the amplitude of vertical change between surface and hyporheic water may reach 200 and~400 μS/cm of specific conductance in two different water bodies of the Rhône River system; Dole-Olivier, 1998;Dole-Olivier et al, 1997).…”
Section: Other Parametersmentioning
confidence: 63%